2007
DOI: 10.1038/sj.eye.6702829
|View full text |Cite
|
Sign up to set email alerts
|

Position of myopic iris-claw phakic intraocular lens by Scheimpflug photography and ultrasound biomicroscopy

Abstract: Purpose To evaluate the position of iris-claw phakic intraocular lens (ICPIOL) in highly myopic eyes by Scheimpflug photography (SP) and ultrasound biomicroscopy (UBM). Methods Nine eyes of five patients aged 31710 years with average spherical equivalent of À16.0475.46 D (range À7.88 to À 22.88 D) were enrolled in this prospective study and implanted with Verisyse ICPIOLs (AMO). The anterior segment was evaluated by SP and UBM preoperatively and for at least 1 month postoperatively. The statistical significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Nakakura [22] found that Pentacam measured significantly higher ACD value than UBM in healthy people. Yu [23] reported no significant difference between Pentacam and UBM in highly myopic eyes. On contrary, Nemeth [20] showed that Pentacam and UBM measured the same ACD values in phakic eyes, but Pentacam measured significantly shallower ACD values in pseudophakic eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Nakakura [22] found that Pentacam measured significantly higher ACD value than UBM in healthy people. Yu [23] reported no significant difference between Pentacam and UBM in highly myopic eyes. On contrary, Nemeth [20] showed that Pentacam and UBM measured the same ACD values in phakic eyes, but Pentacam measured significantly shallower ACD values in pseudophakic eyes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they observed haptic indentation of the iris. Using the Pentacam device and UBM, Yu et al 23 found that space was maintained between iris-fixated pIOLs and the corneal endothelium, angle, and crystalline lens in eyes with high myopia. In our study, the anterior chamber angle narrowed more than 5 degrees in 19 of 20 eyes (95%) after implantation of an iris-fixated pIOL.…”
Section: Discussionmentioning
confidence: 98%
“…Postoperatively, the position of the phakic IOL haptics as well as the distances from corneal endothelium to phakic IOL and from phakic IOL to crystalline lens can also be evaluated. [20][21][22][23][24][25]…”
Section: Phakic Intraocular Lensesmentioning
confidence: 99%